KAJIAN ARITMATIKA SOSIAL DALAM PERHITUNGAN ILMU FARAIDH (ILMU WARIS ) DALAM QS.AN-NISA - Aminah, Siti; Yazidah, Nok Izatul (Universitas Insan Budi Utomo, 2018)
One of the general sciences that has a relationship with al quran is mathematics. This study aims to examine social arithmetic in the calculation of faraidh knowledge in the Surah An-Nisa. The analysis is intended to know and understand contextually the Surah An-Nisa which is closely related to the faraidh contained therein. In this study using qualitative descriptive methods. This type of research is literature study. The subjects in this study are social arithmetic and faraidh, while the object in this research is the Al-Quran. The procedures carried out to collect data in this study include documentation documentation studies and focused discussions. The results of this study indicate that in Surah An-Nisa which consists of 176 ayah, it can be concluded that there are nine ayah in Surah An-Nisa which explains the science of faraidh. The ten ayah referred to are: Surah An-Nisa ayah: 7, 8, 9, 11, 12, 13, 14, 33, and ayah 176. So, the remaining 167 ayah do not explain faraidh. As previously explained, there are nine ayah in the Surah An-nisa which explain faraidh, which is also social arithmetic.